PROFIL KEMAMPUAN LITERASI SAINS CALON GURU BIOLOGI DI UNIVERSITAS BORNEO TARAKAN - Aidil Adhani; Basnawati Basnawati; Zulfadli Zulfadli; Clara Maria Ariesta; Mia Siska; Suhaya Suhaya; Tricirisna Prakash Ramadhan (Biopedagogia, 2020)
PISA defines the definition of scientific literacy as the ability to use scientific knowledge, identify problems, and draw conclusions based on evidence, in order to understand and make decisions about nature and the changes that occur in nature as a result of human activities (Rustaman, 2006; New South Wales Department of Education and Communities, 2011; Gormally et al., 2012). Students as prospective biology teachers must have good scientific literacy. This scientific literacy must be possessed by prospective biology teacher students for better learning for future generations. This study aims to determine the profile of understanding the scientific literacy of prospective biology teachers at the University of Borneo Tarakan. The research method used is descriptive with a quantitative descriptive approach, because the research conducted describes the scientific literacy profile of prospective biology teachers at Borneo Tarakan University. The sampling technique used is random sampling. Descriptive research is a research that describes according to the facts that exist about a natural thing (Sukmadinata, 2011). Based on the research that has been done, it can be concluded that the percentage of good scores contained in the indicators identifies scientific opinions that are valid 70%, and effective literature searches 74.4%. There is enough percentage on the indicator to understand and interpret basic statistics with a value of 54.4%. And indicators 3, 5, 6, and aim are classified as very less. The average score of scientific literacy for all indicators is 49.71% with a very poor category. Keywords:  profile, science literacy, teacher candidate, biology.